Enhanced nitrogen removal via Yarrowia lipolytica-mediated nitrogen and related metabolism of Chlorella pyrenoidosa from wastewater - Zhong, Yuming; Lin, Danni; Li, Sufen; Wang, Qin; Liu, Hui; Ma, Lukai; Liu, Huifan (Frontiers in Bioengineering and Biotechnology, 2023)
We investigated the optimum co-culture ratio with the highest biological nitrogen removal rate, revealing that chemical oxygen demand, total nitrogen (TN), and ammoniacal nitrogen (NH3-N) removal was increased in the C. pyrenoidosa and Y. lipolytica co-culture system at a 3:1 ratio. Compared with the control, TN and NH3-N content in the co-incubated system was decreased within 2–6 days. We investigated mRNA/microRNA (miRNA) expression in the C. pyrenoidosa and Y. lipolytica co-culture after 3 and 5 days, identifying 9885 and 3976 differentially expressed genes (DEGs), respectively. Sixty-five DEGs were associated with Y. lipolytica nitrogen, amino acid, photosynthetic, and carbon metabolism after 3 days. Eleven differentially expressed miRNAs were discovered after 3 days, of which two were differentially expressed and their target mRNA expressions negatively correlated with each other. These miRNAs may further contribute to the activation of target mRNAs. miRNA/mRNA expression profiles confirmed the synergistic effects of a co-culture system on pollutant disposal.